iTherapy: an automated web-based therapy plan for learning disability children - Zakaria, Noor Azura; Abdul Rahman, Nur’Izzah; Abdul Malek, Muhammad Naim (Kulliyyah of Information and Communication Technology International Islamic University Malaysia, 2022)
iTherapy is an automatedweb-based system for the head of therapist and therapist of Penawar Special Learning Centre (PSLC) to produce atherapy plan automatically. PSLC is a centre that assists children with learning disabilities in overcoming their problems by providing a set of therapy treatments. They have nine branches all over Malaysia. It is a stressful job for the therapists to key in all the information in a paper-based approach and using WhatsApp communication to get approval from the head of therapist since there are more than 3000 patients to be analysed. To develop the iTherapy system, an iterative development methodology is used. The development code for the website has been done by using Visual Code Studio and XAMPP as a localhost to deploy the project, Hyper Text Markup Language (HTML), Cascading Style Sheets (CSS) for frontend development while Structured Query Language (MYSQL) to construct the database framework and Hypertext Preprocessor (PHP) as backend development. This system allows the head of therapist and therapists to do patient diagnosis, view therapy plan, get approval and print the approved therapy plan. It is hoped, iTherapy will help the head of therapist and therapist in PSLC to solve their current issues with paper-based approach.For future works, a proper system evaluation can be conducted, and the system can be enhanced by having the knowledge repository.